Investigating Students' Perceptions of Health Informatics Education: What Action Needs to Be Taken? - Anas Ali Alhur; Khalid Abdullatif Alhashash (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
Curriculum evaluation is critical to identify the weaknesses and strengths. Measuring students' satisfaction and analyzing their experiences is an effective tool for curriculum development. Purpose: Evaluate Health Informatics (HI) curriculum from learners' experience in multiple universities in Saudi Arabia. Methods: a cross-sectional study using a survey distributed via Twitter, WhatsApp, and Telegram. Result: a total of (N = 252) participants, Male and Female, with different universities and study levels (Diploma, Bachelor, and Master's) were involved in the study. Among the total number of participants (252), female participants (153) are higher than male participants (99). Furthermore, 79% (200 out of 253) of the students experienced psychological pressure and a lack of understanding of the field. 43.7% (110 out of 252) indicated that the time compatible to finish chapters in the courses. Conclusion: On a national and international scale, health informatics education faces several challenges; required actions to improve the curriculum must be evaluated continuously to achieve the goals and objectives.